Butterhead lettuce growth under shallow water tables and its recovery on tropical urban ecosystem - Strayker Ali Muda; Benyamin Lakitan; Fitri Ramadhani; Juwinda (Advances in Horticultural Science)
Butterhead lettuce (Lactuca sativa var. capitata) is a nutrient-rich leafy vegetable beneficial for human health. Lettuce growth and yield performance hampered under water stress conditions. This study aimed to assess its growth and recovery under short-term shallow water conditions in the tropical urban ecosystem. A randomized block design was used with three water table treatments: 16.7 cm, 12.7 cm, and 9.7 cm from the substrate surface. The Results showed that butterhead lettuce is intolerant of excess water, with stunted growth at the 9.7 cm water level, by affecting leaf length, leaf width, leaf initiation, and canopy area. Substrate moisture also indicated excess water at this level. Optimal recovery was observed two weeks after water stress. Leaf length and leaf width were analyzed using zero-intercept linear regression and the results were reliable predictors of leaf area (y = 0.6076LLxLW; R² = 0.9694). In conclusion, butterhead lettuce is sensitive to excess water, as shown by morphological changes, and requires two weeks to recover after water stress.